Multi-stakeholder and innovation platforms: Group reports from the IFWF3 - International Livestock Research Institute (International Livestock Research Institute, 2011)
One of the 'learning to innovate' sessions in the 2011 Third International Forum on Water and Food looked at experiences within the CPWF with multi-stakeholder Platforms (MSP) and Innovation Platforms (IP). This video has the group reports that discussed: 1) How do we scale out such platform processes? 2) What are the most significant lessons and messages in this area for 'research for development'? 3) What is new and innovative in the experiences shared? and 4) What are the research questions on platforms that could be addressed across CPWF Basins?